Groundwater temperature anomalies in central Europe. (15th October 2019) - Tissen, Carolin; Benz, Susanne A; Menberg, Kathrin; Bayer, Peter; Blum, Philipp
Abstract: As groundwater is competitively used for drinking, irrigation, industrial and geothermal applications, the focus on elevated groundwater temperature (GWT) affecting the sustainable use of this resource increases. Hence, in this study GWT anomalies and their heat sources are identified. The anthropogenic heat intensity (AHI), defined as the difference between GWT at the well location and the median of surrounding rural background GWTs, is evaluated in over 10 000 wells in ten European countries. Wells within the upper three percentiles of the AHI are investigated for each of the three major land cover classes (natural, agricultural and artificial). Extreme GWTs ranging between 25 °C and 47 °C are attributed to natural hot springs. In contrast, AHIs from 3 to 10 K for both natural and agricultural surfaces are due to anthropogenic sources such as landfills, wastewater treatment plants or mining. Two-thirds of all anomalies beneath artificial surfaces have an AHI > 6 K and are related to underground car parks, heated basements and district heating systems. In some wells, the GWT exceeds current threshold values for open geothermal systems. Consequently, a holistic management of groundwater, addressing a multitude of different heat sources, is required to balance the conflict between groundwater quality for drinking and groundwater as an energy source or storage media for geothermal systems.